Aspects of Justice, Legal Certainty and Benefit in the Settlement of Patent Disputes - Ritonga, Moehammad Mahastar; Jaya, Febri; Sudirman, Lu (Batulis Civil Law Review, 2024)
Introduction: Patent rights are rights granted to individuals who have successfully created new inventions, where the rights and responsibilities of the inventor arise when the invention is registered in accordance with applicable regulations and protected by Law Number 13 of 2016 concerning patents. In the resolution of patent disputes, the regulations mandate the use of litigation remedies. Nonetheless, it is important to remember that mediation is an alternative dispute resolution before taking litigation steps, and is a win-win solution, but it is not a mandatory stage in the settlement of patent civil disputes. Of course, this is contrary to the implementation of the legal aspects which are not only justice, and legal certainty but also expediency.Purposes of the Research: This research aims to improve understanding of the implementation of the legal objectives aspect in patent dispute resolution in Indonesia.Methods of the Research: In this research, normative legal research methods were used. The data taken consists of primary legal materials and secondary legal materials.Results of the Research: The results of this study reveal a new perspective on the concept of justice, which was previously only seen as "right and wrong", to "risks and benefits". This is due to the principle of expediency that lies between the point of legal certainty and the point of justice.